Stability and monotonicity of Lotka–Volterra type operators - Mukhamedov, Farrukh; Saburov, Mansoor (Springer International Publishing, 2017)
In the present paper,we investigate stability of trajectories ofLotka–Volterra (LV) type operators defined in finite dimensional simplex.We prove that any LV type operator is a surjection of the simplex. It is introduced a newclass of LV-type operators, called MLV type ones, and we show that trajectories of the introduced operators converge. Moreover, we show that such kind of operators have totally different behavior than f-monotone LV type operators.